2007
DOI: 10.1007/s11255-007-9304-9
|View full text |Cite
|
Sign up to set email alerts
|

Is deep dorsal vein arterialization effective in elderly patients?

Abstract: DDVA could successfully be performed for carefully selected elderly patients as long as the presence of risk factors for ED are ruled out.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…These data stay in contrast to a further study, published in 2008 [17]. Kayigil et al defined subjective success after pure venous arterialization as a score increase of at least 5 points noted postoperatively in the five-item version of the IIEF (IIEF-5).…”
Section: Results Of Penile Revascularizationmentioning
confidence: 71%
“…These data stay in contrast to a further study, published in 2008 [17]. Kayigil et al defined subjective success after pure venous arterialization as a score increase of at least 5 points noted postoperatively in the five-item version of the IIEF (IIEF-5).…”
Section: Results Of Penile Revascularizationmentioning
confidence: 71%
“…Similarly, in 2005, the AUA Update on the Management of ED [25] , and the International Society for Sexual Medicine textbook, Standard Practice in Sexual Medicine [26] maintained the consensus. However, it might deserve reappraisal after a review of arterial reconstructions reported after 2004 ( Table 2 ) [27–32] , Interestingly, researchers unexceptionally report positive long-term outcomes when both penile arterial and venous reconstruction are incorporated, suggesting that arterial reconstruction alone is insufficient for the long-term restoration of erectile function. For investigating the vascular contribution exclusively, haemodynamic studies have been used in both fresh and defrosted human male cadavers since 2001 [33] .…”
Section: A Review Of Arterial Revascularisation/veno-arterialisation mentioning
confidence: 99%
“…However, in spite of all these admonitions, a review of the recent literature on this subject between 2003 and the present time of this writing shows there have been several publications on virtually every aspect of CVOD: basic science and hemodynamics [124][125][126][127], pathogenesis [128][129][130][131][132], investigations [127,133], surgery [111,[134][135][136][137][138][139][140], prognosis [141,142], and post-operative changes [143].…”
Section: Levels Of Evidencementioning
confidence: 99%
“…Surprisingly, there has only been one retrospective case series published in the literature since 2003 [111]. The lack of further studies may reflect consensus opinion, such as American Urological Association (AUA) guidelines [68] which state that, “Treatment of vasculogenic ED by penile arterial revascularization has been performed using a variety of microvascular procedures for the past 30 years.…”
Section: Arterial Revascularizationmentioning
confidence: 99%
See 1 more Smart Citation